The entrepreneurship of Spanish rural women: analysis of the wage gap. A difficult reality to solve - Millán-Vázquez de la Torre, María del Cisne Genoveva; Velasco-Portero, María del Cisne Teresa; Ramírez-Sobrino, Jesús Nicolás (Papeles de Población, 2018)
In rural areas, Spanish women sometimes develop a work not recognized by society. Lack of awareness of their empowerment lead them to work in jobs which not correspond to their training (temporary contracts, part-time jobs); which makes its economy be at disadvantage compared to men. in this article was analyzed the wage gap through field work. In addition, with a logit model, was studied probability that a woman depending on their socioeconomic characteristics can become an entrepreneur in rural areas. Intending to know their entrepreneurial capacity that will make them occupationally equal, could reduce the wage gap and will prevent future poverty.